Targetable genes associated with hematogenous metastasis in gastric cancer using the TCGA database - Jaeun Yoo; Hyun Myong Kim; Kyoungyun Jeong; Yie-Ri Yoo; Ji-Yeon Shin; Seungho Lee; Seungbok Lee; Hye Seung Lee; Kyoung Un Park; Seong-Ho Kong; Do Joong Park; Hyuk-Joon Lee; et al. (Korean Journal of Clinical Oncology, 2026)
Purpose: Gastric cancer is a major global health issue, especially in advanced stages with metastasis. However, anti-angiogenic treatments such as ramucirumab target vascular endothelial growth factor, yet the exact mechanisms behind hematogenous metastasis remain unclear. This study analyzed RNA sequencing data from TCGA to identify angiogenesis-related genes in metastatic gastric cancer.Methods: Patients were categorized into four metastasis types (non-metastasis, hematogenous, locoregional, and lymphatic) based on clinical data. cBioPortal was used to identify frequently mutated genes across five metastatic cancer studies. RNA sequencing and clinical data were obtained from the TCGA-STAD project. RNA expression levels were compared across metastasis groups using independent-samples t-tests, followed by false discovery rate adjustment for multiple comparisons.Results: RNA expression analysis was performed using a 132-gene analytical panel in the TCGA-STAD cohort. Among the 95-gene angiogenesis/metastasis-related genes represented in this panel, RAF1, ARID1A, ERBB3, FGFR3, BAP1, TSC2, and KDR showed nominal expression differences in comparisons involving the hematogenous metastasis group. None of these differences remained statistically significant after false discovery rate correction.Conclusion: In this exploratory analysis, several candidate genes with prior literature support showed nominal expression differences in comparisons involving hematogenous metastasis in gastric cancer. These findings are hypothesis-generating and require validation in independent cohorts and functional studies.